2021
DOI: 10.52586/s555
|View full text |Cite
|
Sign up to set email alerts
|

Review article on COVID-19 and Guillain-Barré syndrome

U. Juhi Patnaik

Abstract: The tale COVID infection pandemic or as far as we might be concerned better, COVID-19, has assaulted society on a worldwide scale. For the unenlightened, the sickness is brought about by the specific infection Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). It is only from time to time that we have a pandemic seething on that has carried with itself a particularly humongous size of harm and on each and every front of the human culture, be it clinical, practical, social or pretty much anything. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…59,60 Campylobacter jejuni is the likely the most common infection causing Guillain-Barré syndrome. 13 In most patients, the delay between the development of infectious and neurological symptoms and a negative PCR supports a post-infectious rather than a direct infectious cause. The role of the peripheral nervous system in the development of GBS in SARS-CoV-2-infected patients is uncertain.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…59,60 Campylobacter jejuni is the likely the most common infection causing Guillain-Barré syndrome. 13 In most patients, the delay between the development of infectious and neurological symptoms and a negative PCR supports a post-infectious rather than a direct infectious cause. The role of the peripheral nervous system in the development of GBS in SARS-CoV-2-infected patients is uncertain.…”
Section: Discussionmentioning
confidence: 98%
“…57 Most of the patients have symptoms of infection in preceding 3-6 weeks. (13) Some studies have shown that bacterial and viral pathogens have been discovered in GBS patients, but the factors that cause immune-mediated nerve tissue destruction have not been identified. 58 The Epstein-Barr virus, CMV, Campylobacter jejuni, human immunodeficiency virus (HIV), and ZiKa virus are among the pathogenic agents linked to GBS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations